Évaluation des effets dynamiques de la croissance économique, de la consommation d’énergie fossile, de la productivité agricole, et du tourisme sur les émissions de CO2 à la Dominique - Louis Dupont (Études Caribéennes)
The climate change is today an important challenge for humanity. Facing the flail, most countries try to conciliate adaptation to climate change and sustainable development. In this context, the goal of this study is to analyse in the case of Dominica, the relationship between the CO2 emissions per capita and important economic variables for the environment, such as economic growth, agricultural productivity, tourism activity, and fossil fuel energy use. The choice of Dominica as study rests on the fact that Dominica is planned to be the nation of the world most resilient to climate change in 2030. Would this goal be attained? In order to verify, an ARDL model is used to evaluate the dynamic effects of these variables on CO2 emissions in Dominica. The empirical findings revealed that, while economic growth, the use of fuel energy, and tourism activity contribute to environmental damage by cumulative CO2 emissions in Dominica. However, agricultural productivity help to improve the environment quality by lowering CO2 emissions. Similar results were obtained using alternative estimator such as, fully modified least squares (FMOLS). Furthemore, the pairwise Granger causality test was used to determine the causal relationship between the variables. Finally, to reach the goal of Dominica authorities, four conditions must be met: (i) an economy with less carbon, (ii) an eco-efficient tourism, resting on carrying capacity, in order to find a balance between population and visitors number, (iii) an energy mix, composed mainly of clean energies such as solar, wind, and geothermy, and (iv) a natural agriculture, ecologically, economicaly, and socialy responsible.